Evaluation of the pharmacokinetics, dosimetry, and therapeutic efficacy for the α-particle-emitting transarterial radioembolization (αTARE) agent [225Ac]Ac-DOTA-TDA-Lipiodol® against hepatic tumors - Anders Josefsson; Angel G. Cortez; Harikrishnan Rajkumar; Joseph D. Latoche; Ambika P. Jaswal; Kathryn E. Day; Mohammadreza Zarisfi; Lora H. Rigatti; Ziyu Huang; Jessie R. Nedrow (SpringerOpen, 2023)
Abstract Background The liver is a common site for metastatic disease for a variety of cancers, including colorectal cancer. Both primary and secondary liver tumors are supplied through the hepatic artery while the healthy liver is supplied by the portal vein. Transarterial radioembolization (TARE) using yttrium-90 glass or resin microspheres have shown promising results with reduced side-effects but have similar survival benefits as chemoembolization in patients with hepatocellular carcinoma (HCC). This highlights the need for new novel agents against HCC. Targeted alpha therapy (TAT) is highly potent treatment due to the short range (sparing adjacent normal tissue), and densely ionizing track (high linear energy transfer) of the emitted α-particles. The incorporation of α-particle-emitting radioisotopes into treatment of HCC has been extremely limited, with our recent publication pioneering the field of α-particle-emitting TARE (αTARE). This study focuses on an in-depth evaluation of the αTARE-agent [225Ac]Ac-DOTA-TDA-Lipiodol® as an effective therapeutic agent against HCC regarding pharmacokinetics, dosimetry, stability, and therapeutic efficacy. Results [225Ac]Ac-DOTA-TDA was shown to be a highly stable with bench-top stability at ≥ 95% radiochemical purity (RCP) over a 3-day period and serum stability was ≥ 90% RCP over 5-days. The pharmacokinetic data showed retention in the tumor of [225Ac]Ac-DOTA-TDA-Lipiodol® and clearance through the normal organs. In addition, the tumor and liver acted as suppliers of the free daughters, which accumulated in the kidneys supplied via the blood. The dose limiting organ was the liver, and the estimated maximum tolerable activity based on the rodents whole-body weight: 728-3641 Bq/g (male rat), 396-1982 Bq/g (male mouse), and 453-2263 Bq/g (female mouse), depending on an RBE-value (range 1-5). Furthermore, [225Ac]Ac-DOTA-TDA-Lipiodol® showed significant improvement in survival for both the male and female mice (median survival 47-days) compared with controls (26-days untreated, and 33-35-days Lipiodol® alone). Conclusions This study shows that [225Ac]Ac-DOTA-TDA-Lipiodol® is a stable compound allowing for centralized manufacturing and distribution world-wide. Furthermore, the result of this study support the continue development of evaluation of the αTARE-agent [225Ac]Ac-DOTA-TDA-Lipiodol® as a potential treatment option for treating hepatic tumors.